Muscle memory - Abdullah, Nasiha; Abdul Talib, Nurafida; Adenan, Nur Dalila; Mohamad Azmin, Nur Azwani; Ngah, Nazlin Emieza (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2024)
Muscle memory is a type of procedural memory that includes repeating a specific motor task in order to consolidate information into memory; it is sometimes used interchangeably with motor learning. When a movement is repeated over time, the brain develops long-term muscle memory for it, allowing it to be executed with little to no conscious effort. This procedure reduces the requirement for attention and increases the efficiency of the motor and memory systems. Many everyday activities, such as riding bikes, driving cars, playing ball sports, typing on keyboards, entering PINs, playing musical instruments, gambling, martial arts, swimming, dancing, and sketching, are using muscle memory.